Binder composition for power storage device, slurry for power storage device electrode, power storage device electrode, and power storage device
Patent Information
- Application Number
- JP2023142136
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
AI Technical Summary
【0023】 本発明に係る蓄電デバイス用バインダー組成物によれば、表面状態、密着性及びイオン伝導性に優れた蓄電デバイス電極を作製することができ、ひいては蓄電デバイスのサイクル寿命特性を向上させることができる。
Smart Images

Figure 2025035223000001 
Figure 2025035223000002 
Figure 2025035223000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a binder composition for an electricity storage device, a slurry for an electricity storage device electrode, an electricity storage device electrode, and an electricity storage device. [Background technology]
[0002] In recent years, there has been a demand for power storage devices having high voltage and high energy density as power sources for driving electronic devices. Lithium ion batteries and lithium ion capacitors are expected to be such power storage devices.
[0003] The electrodes used in such an electricity storage device are manufactured by applying a composition (slurry for electricity storage device electrodes) containing an active material and a polymer that functions as a binder to the surface of a current collector and drying it. The properties required of the polymer used as a binder include the ability to bind active materials together and the ability to adhere to the current collector. In addition, the polymer must have resistance to powdering, so that fine powder of the active material does not fall off from the active material layer when cutting the applied and dried composition coating film (hereinafter also referred to as the "active material layer"). Such a binder material exhibits good adhesion and reduces the internal resistance of the battery caused by the binder material, thereby imparting good charge and discharge characteristics to the electricity storage device.
[0004] It has been empirically demonstrated that the binding ability between the active materials, the adhesion ability between the active material and the current collector, and the resistance to powder falling off are almost proportional to the performance, and therefore, in the present specification, these may be collectively referred to as "adhesion".
[0005] Recently, in order to manufacture electrochemical devices with excellent capacity and charge / discharge cycle characteristics, the use of positive electrode active materials with high reactivity with water has been considered. Polyvinylidene fluoride (PVDF) is the most widely used binder for organic solvent-based storage device electrodes. Although PVDF has good binding properties and oxidation resistance, it contains fluorine atoms, which causes a high environmental load, and the instability of raw material supply is becoming apparent (for example, see Patent Document 1).
[0006] Under these circumstances, various binder materials have been proposed to solve the various problems associated with positive electrode slurries (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 10-298386 [Patent Document 2] JP 2019-194944 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, in the method using a positive electrode slurry containing conventional PVDF or sulfonated PVDF disclosed in the above Patent Document 1, it is known that crosslinks are formed due to the removal of HF, especially under basic conditions. If this crosslink is formed in the positive electrode slurry, adhesion may be impaired. In addition, when the conventional positive electrode slurry is applied, craters may be generated on the surface of the coating due to bubble breakage due to the effect of emulsifiers remaining in the slurry. Such surface defects can affect the product yield. This must be prevented as it will lead to a decline in productivity.
[0009] Some aspects of the present invention provide a binder composition for an electricity storage device that can produce an electricity storage device electrode having excellent surface condition, adhesion, and ion conductivity, and can improve the cycle life characteristics of the electricity storage device. [Means for solving the problem]
[0010] The present invention has been made to solve at least a part of the above-mentioned problems, and can be realized in any of the following aspects.
[0011] One aspect of the binder composition for an electrical storage device according to the present invention is The composition comprises a polymer (A), a nonionic surfactant (B), and a liquid medium (C), When the total amount of repeating units contained in the polymer (A) is taken as 100 mass %, the polymer (A) 1 to 50 mass% of a repeating unit (a1) derived from an α,β-unsaturated nitrile compound; 25 to 75 mass% of a repeating unit (a2) derived from a conjugated diene compound; Contains the content of the nonionic surfactant (B) is 0.1 to 10 parts by mass relative to 100 parts by mass of the polymer (A); The liquid medium (C) is at least one selected from the group consisting of aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, ketones, esters, ethers, and lactams.
[0012] In one embodiment of the binder composition for an electricity storage device, The polymer (A) is a polymer particle, The number average particle size of the polymer particles may be 50 nm or more and 1,000 nm or less.
[0013] In any one of the embodiments of the binder composition for an electricity storage device, The polymer (A) may further contain 0.1 to 10% by mass of a repeating unit (a3) derived from an unsaturated carboxylic acid.
[0014] In any one of the embodiments of the binder composition for an electricity storage device, The polymer (A) may further contain 1 to 50% by mass of a repeating unit (a4) derived from an aromatic vinyl compound.
[0015] In any one of the embodiments of the binder composition for an electricity storage device, The polymer (A) may further contain 0.1 to 10% by mass of a repeating unit (a6) derived from (meth)acrylamide.
[0016] In any one of the embodiments of the binder composition for an electricity storage device, The polymer (A) may further contain 0.1 to 10% by mass of a repeating unit (a7) derived from a compound having a sulfonic acid group.
[0017] One embodiment of a slurry for an electric storage device electrode according to the present invention is The binder composition for an electricity storage device according to any one of the above aspects and an active material are contained therein.
[0018] In one embodiment of the slurry for an electricity storage device electrode, It may further contain a thickening agent.
[0019] In any one of the embodiments of the slurry for an electricity storage device electrode, The active material may be a positive electrode active material.
[0020] In any one of the embodiments of the slurry for an electricity storage device electrode, The positive electrode active material may be an olivine-type lithium-containing phosphate compound.
[0021] One aspect of the electricity storage device electrode according to the present invention is The electrode comprises a current collector, and an active material layer formed by applying the slurry for an electricity storage device electrode according to any one of the above aspects to the surface of the current collector and drying the applied active material layer.
[0022] One aspect of the electricity storage device according to the present invention is The power storage device includes the electrode according to the above aspect. Effect of the Invention
[0023] According to the binder composition for an electricity storage device of the present invention, it is possible to prepare an electricity storage device electrode having excellent surface condition, adhesion and ion conductivity, and thus to improve the cycle life characteristics of the electricity storage device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Preferred embodiments of the present invention will be described in detail below. Note that the present invention is not limited to the embodiments described below, and should be understood to include various modified examples that are implemented within the scope of the present invention.
[0025] In this specification, "(meth)acrylic acid-" refers to "acrylic acid-" or "methacrylic acid-", "-(meth)acrylate" refers to "-acrylate" or "-methacrylate", and "(meth)acrylamide" refers to "acrylamide" or "methacrylamide".
[0026] In this specification, a numerical range described as "X to Y" is interpreted as including the numerical value X as the lower limit and including the numerical value Y as the upper limit.
[0027] 1. Binder composition for power storage devices The binder composition for an electric storage device according to one embodiment of the present invention contains a polymer (A), a nonionic surfactant (B), and a liquid medium (C). The polymer (A) contains 1 to 50 mass% of repeating units (a1) derived from an α,β-unsaturated nitrile compound and 25 to 75 mass% of repeating units (a2) derived from a conjugated diene compound, when the total of the repeating units contained in the polymer (A) is taken as 100 mass%. The content of the nonionic surfactant (B) is 0.1 to 10 parts by mass with respect to 100 parts by mass of the polymer (A). The liquid medium (C) is at least one selected from the group consisting of aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, ketones, esters, ethers, and lactams. The components contained in the binder composition for an electric storage device according to this embodiment will be described in detail below.
[0028] 1.1. Polymer (A) The binder composition for a storage battery device according to this embodiment contains a polymer (A). The polymer (A) is preferably a particle dispersion dispersed in a liquid medium (C) described later. When the polymer (A) is dispersed in the liquid medium (C), the stability of the composition (hereinafter also referred to as "slurry") prepared by mixing the polymer (A) with the active material is improved, and the coating property of the slurry on the current collector is also improved, which is preferable. In addition, the presence of a particulate binder makes the active material slippery during pressing, and makes it easier to increase the density. Furthermore, excessive coating on the conductive assistant can be suppressed, and a good conductive path can be formed.
[0029] The repeating units constituting the polymer (A), the physical properties of the polymer (A), and the production method thereof will be described below in that order.
[0030] 1.1.1. Repeating units constituting polymer (A) The polymer (A) contains 1 to 50 mass% of repeating units (a1) (hereinafter also referred to as "repeating units (a1)") derived from an α,β-unsaturated nitrile compound and 25 to 75 mass% of repeating units (a2) (hereinafter also referred to as "repeating units (a2)") derived from a conjugated diene compound, when the total of the repeating units contained in the polymer (A) is taken as 100 mass%. In addition to the repeating units (a1) and (a2), the polymer (A) may contain repeating units derived from other monomers copolymerizable therewith.
[0031] 1.1.1.1. Repeating unit (a1) derived from an α,β-unsaturated nitrile compound The content of the repeating unit (a1) derived from an α,β-unsaturated nitrile compound is 1 to 50% by mass, when the total of the repeating units contained in the polymer (A) is taken as 100% by mass. The lower limit of the content of the repeating unit (a1) is preferably 2% by mass, more preferably 3% by mass. The upper limit of the content of the repeating unit (a1) is preferably 48% by mass, more preferably 45% by mass. When the polymer (A) contains the repeating unit (a1) within the above range, the affinity between the polymer (A) and the liquid medium (C) is improved, and the polymer (A) is more likely to maintain its particle shape. In addition, the affinity between the polymer (A) and the electrolyte is improved, and an increase in internal resistance due to the polymer (A) becoming an electric resistance component in an electricity storage device can be suppressed.
[0032] The α,β-unsaturated nitrile compound is not particularly limited, and examples thereof include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethylacrylonitrile, vinylidene cyanide, etc., and one or more selected from these can be used. Among these, one or more selected from the group consisting of acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is particularly preferred.
[0033] 1.1.1.2. Repeating units derived from conjugated diene compounds (a2) The content of the repeating unit (a2) derived from a conjugated diene compound is 25 to 75% by mass when the total of the repeating units contained in the polymer (A) is 100% by mass. The lower limit of the content of the repeating unit (a2) is preferably 27% by mass, more preferably 30% by mass. The upper limit of the content of the repeating unit (a2) is preferably 73% by mass, more preferably 70% by mass. When the polymer (A) contains the repeating unit (a2) within the above range, the dispersibility of the active material and the filler is improved, and a homogeneous active material layer and a protective film can be prepared, so that the structural defects of the electrode plate are eliminated and good repeated charge and discharge characteristics are exhibited. In addition, the polymer (A) covering the surface of the active material can be given elasticity, and the polymer (A) can be stretched to improve adhesion, so that good charge and discharge durability characteristics are exhibited.
[0034] The conjugated diene compound is not particularly limited, but includes 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, etc., and one or more selected from these can be used. Among these, 1,3-butadiene is particularly preferred.
[0035] 1.1.1.3. Other repeating units The polymer (A) may contain, in addition to the repeating units (a1) and (a2), a repeating unit derived from another monomer copolymerizable therewith. Examples of such a repeating unit include a repeating unit (a3) derived from an unsaturated carboxylic acid (hereinafter, referred to as "repeating unit"). Repeating units (a3) derived from an aromatic vinyl compound (a4) (hereinafter also referred to as "repeating unit (a4)"), repeating units (a5) derived from an unsaturated carboxylic acid ester (a5) (hereinafter also referred to as "repeating unit (a5)"), repeating units (a6) derived from (meth)acrylamide (a6) (hereinafter also referred to as "repeating unit (a6)"), repeating units (a7) derived from a compound having a sulfonic acid group (a7) (hereinafter also referred to as "repeating unit (a7)"), and repeating units derived from a cationic monomer.
[0036] <Repeating Unit (a3) Derived from Unsaturated Carboxylic Acid> The polymer (A) may contain a repeating unit (a3) derived from an unsaturated carboxylic acid. The content of the repeating unit (a3) derived from an unsaturated carboxylic acid is preferably 0.1 to 10% by mass, when the total of the repeating units contained in the polymer (A) is taken as 100% by mass. The lower limit of the content of the repeating unit (a3) is more preferably 0.5% by mass, and particularly preferably 1% by mass. The upper limit of the content of the repeating unit (a3) is more preferably 9% by mass, and particularly preferably 8% by mass. When the polymer (A) contains the repeating unit (a3) within the above range, the adhesion between the current collector and the active material layer can be improved, and the adhesion strength of the electrode may be improved.
[0037] The unsaturated carboxylic acid is not particularly limited, but includes monocarboxylic acids and dicarboxylic acids (including anhydrides) such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, etc., and one or more selected from these can be used. Among these, it is preferable to use one or more selected from acrylic acid, methacrylic acid, and itaconic acid.
[0038] <Repeating unit (a4) derived from aromatic vinyl compound> The content of the repeating unit (a4) derived from an aromatic vinyl compound is preferably 1 to 50% by mass, when the total of the repeating units contained in the polymer (A) is taken as 100% by mass. The lower limit of the content of the repeating unit (a4) is more preferably 3% by mass, and particularly preferably 5% by mass. The upper limit of the content of the repeating unit (a4) is more preferably 47% by mass, and particularly preferably 45% by mass. By containing the repeating unit (a4) in the polymer (A) within the above range, fusion between the polymers (A) dispersed in the active material layer is suppressed, good slurry properties are exhibited, and the coating properties can be improved. In addition, the permeability of the electrolyte can be improved, and therefore good repeated charge / discharge properties may be exhibited.
[0039] The aromatic vinyl compound is not particularly limited, but may be styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, chlorostyrene, divinylbenzene, etc., and one or more selected from these may be used. Among these, styrene is particularly preferred.
[0040] <Repeating Unit (a5) Derived from Unsaturated Carboxylic Acid Ester> The polymer (A) may contain a repeating unit (a5) derived from an unsaturated carboxylate. The content of the repeating unit (a5) derived from an unsaturated carboxylate is preferably 0 to 15% by mass, when the total of the repeating units contained in the polymer (A) is taken as 100% by mass. The lower limit of the content of the repeating unit (a5) is more preferably 1% by mass, and particularly preferably 2% by mass. The upper limit of the content of the repeating unit (a5) is more preferably 12% by mass, and particularly preferably 10% by mass. When the polymer (A) contains the repeating unit (a5) within the above range, the affinity between the polymer (A) and the electrolyte is improved, and an increase in internal resistance due to the polymer (A) becoming an electric resistance component in an electricity storage device may be suppressed.
[0041] Among the unsaturated carboxylic acid esters, (meth)acrylic acid esters can be preferably used. Specific examples of (meth)acrylic acid esters include, for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tri( ...propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, Examples of the acrylate include trimethylolpropane acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, glycerin mono(meth)acrylate, and glycerin di(meth)acrylate, and one or more selected from these can be used. Among these, it is preferable to use one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, ethylene glycol di(meth)acrylate, and 2-hydroxyethyl (meth)acrylate, and methyl (meth)acrylate is particularly preferable.
[0042] <Repeating unit (a6) derived from (meth)acrylamide> The polymer (A) may contain a repeating unit (a6) derived from (meth)acrylamide. The content of the repeating unit (a6) derived from (meth)acrylamide is preferably 0.1 to 10% by mass, when the total of the repeating units contained in the polymer (A) is taken as 100% by mass. The lower limit of the content of the repeating unit (a6) is more preferably 0.5% by mass, and particularly preferably 1% by mass. The upper limit of the content of the repeating unit (a6) is more preferably 9% by mass, and particularly preferably 8% by mass. When the polymer (A) contains the repeating unit (a6) within the above range, the dispersibility of the active material and the filler in the slurry may be improved. In addition, the flexibility of the obtained active material layer may become appropriate, and the adhesion between the current collector and the active material layer may be improved.
[0043] Examples of (meth)acrylamides include, but are not limited to, acrylamide, methacrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N,N-diethylmethacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, N-methylol acrylamide, N-methylol methacrylamide, diacetone acrylamide, and maleic acid amide, and one or more selected from these can be used.
[0044] <Repeating Unit (a7) Derived from a Compound Having a Sulfonic Acid Group> The polymer (A) may contain a repeating unit (a7) derived from a compound having a sulfonic acid group. The content of the repeating unit (a7) derived from a compound having a sulfonic acid group is preferably 0.1 to 10 mass% when the total of the repeating units contained in the polymer (A) is taken as 100 mass%. The lower limit of the content of the repeating unit (a7) is more preferably 0.5 mass%, and particularly preferably 1 mass%. The upper limit of the content of the repeating unit (a7) is more preferably 9 mass%, and particularly preferably 8 mass%. When the polymer (A) contains the repeating unit (a7) within the above range, the dispersibility of the active material and filler is improved, and a homogeneous active material layer and protective film may be obtained. Furthermore, the adhesion between the current collector and the active material layer is improved, and structural defects of the electrode plate are eliminated. In some cases, the battery may exhibit good charge / discharge characteristics.
[0045] The compound having a sulfonic acid group is not particularly limited, but includes compounds such as vinyl sulfonic acid, styrene sulfonic acid, allyl sulfonic acid, sulfoethyl (meth)acrylate, sulfopropyl (meth)acrylate, sulfobutyl (meth)acrylate, 2-acrylamido-2-methylpropanesulfonic acid, acrylamido tert-butylsulfonic acid, 2-hydroxy-3-acrylamidopropanesulfonic acid, 3-allyloxy-2-hydroxypropanesulfonic acid, and alkali salts thereof, and one or more selected from these can be used.
[0046] <Repeating units derived from cationic monomers> The polymer (A) may contain a repeating unit derived from a cationic monomer. The cationic monomer is not particularly limited, but is preferably at least one monomer selected from the group consisting of secondary amines (salts), tertiary amines (salts) and quaternary ammonium salts. Specific examples of cationic monomers include 2-(dimethylamino)ethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate methyl chloride quaternary salt, 2-(diethylamino)ethyl (meth)acrylate, 3-(dimethylamino)propyl (meth)acrylate, 3-(diethylamino)propyl (meth)acrylate, 4-(dimethylamino)phenyl (meth)acrylate, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth)acrylate, 2-(0-[1'-methylpropylideneamino]carboxyamino)ethyl (meth)acrylate, 2-(1-aziridinyl)ethyl (meth)acrylate, methacryloylcholine chloride, tris(2-acryloyloxyethyl) isocyanurate, 2-vinylpiperidinyl, 2-vinylpyridin ... Examples of the amines include lysine, quinaldine red, 1,2-di(2-pyridyl)ethylene, 4'-hydrazino-2-stilbazole dihydrochloride hydrate, 4-(4-dimethylaminostyryl)quinoline, 1-vinylimidazole, diallylamine, diallylamine hydrochloride, triallylamine, diallyldimethylammonium chloride, dichlormid, N-allylbenzylamine, N-allylaniline, 2,4-diamino-6-diallylamino-1,3,5-triazine, N-trans-cinnamyl-N-methyl-(1-naphthylmethyl)amine hydrochloride, trans-N-(6,6-dimethyl-2-hepten-4-ynyl)-N-methyl-1-naphthylmethylamine hydrochloride, and the like. One or more selected from these may be used.
[0047] 1.1.2. Physical properties of polymer (A) <Number average particle diameter> When the polymer (A) is a particle, the number average particle diameter of the particles is preferably 50 nm or more and 1,000 nm or less, more preferably 70 nm or more and 950 nm or less, and particularly preferably 90 nm or more and 900 nm or less. When the number average particle diameter of the particles of the polymer (A) is within the above range, the particles of the polymer (A) are easily adsorbed on the surface of the active material, so that the particles of the polymer (A) can move along with the movement of the active material. As a result, migration can be suppressed, and the deterioration of electrical properties can be reduced in some cases.
[0048] The number average particle size of the polymer (A) particles is the average particle size measured by a concentrated particle size analyzer using dynamic light scattering (DLS). Examples of the concentrated particle size analyzer include "FPA-1000" manufactured by Otsuka Electronics Co., Ltd.
[0049] 1.1.3. Method for producing polymer (A) <Polymerization process> The polymer (A) can be produced by emulsion polymerization in the presence of the nonionic surfactant (B), other emulsifiers, chain transfer agents, polymerization initiators, and the like.
[0050] As the nonionic surfactant (B), one or more compounds selected from the compounds described in "1.2. Nonionic surfactant (B)" described later can be used.
[0051] Other emulsifiers include fluorosurfactants such as sulfate salts of higher alcohols, alkylbenzenesulfonates, alkylnaphthalenesulfonates, alkyldiphenyletherdisulfonates, aliphatic sulfonates, aliphatic carboxylates, dehydroabietic acid salts, naphthalenesulfonic acid-formaldehyde condensates, perfluorobutylsulfonates, perfluoroalkyl group-containing phosphate esters, perfluoroalkyl group-containing carboxylates, and perfluoroalkylethylene oxide adducts, and one or more selected from these can be used.
[0052] As specific examples of the chain transfer agent and polymerization initiator, the compounds described in Japanese Patent No. 5999399 and the like can be used.
[0053] The emulsion polymerization method for synthesizing the polymer (A) may be carried out in a single-stage polymerization or in a multi-stage polymerization of two or more stages.
[0054] When the synthesis of the polymer (A) is carried out by single-stage polymerization, the monomer mixture can be subjected to emulsion polymerization in the presence of the nonionic surfactant (B), other emulsifiers, a chain transfer agent, a polymerization initiator, etc., preferably at a temperature of 0 to 80°C and for a polymerization time of preferably 4 to 36 hours.
[0055] When the synthesis of the polymer (A) is carried out by two-stage polymerization, it is preferable to set the polymerization in each stage as follows.
[0056] The proportion of the monomers used in the first-stage polymerization is preferably in the range of 20 to 99% by mass, more preferably in the range of 25 to 99% by mass, based on the total mass of the monomers (the sum of the mass of the monomers used in the first-stage polymerization and the mass of the monomers used in the second-stage polymerization). By carrying out the first-stage polymerization at such a proportion of the monomers, it is possible to obtain particles of the polymer (A) that are excellent in dispersion stability and are unlikely to form aggregates, and it is also preferable that the viscosity increase over time of the binder composition for an electricity storage device after solidification is suppressed.
[0057] The types and proportions of monomers used in the second-stage polymerization may be the same as or different from the types and proportions of monomers used in the first-stage polymerization.
[0058] From the viewpoint of the dispersibility of the particles of the resulting polymer (A), the polymerization conditions in each stage are preferably as follows. First-stage polymerization: a temperature of preferably 0 to 80° C.; a polymerization time of preferably 2 to 36 hours; a polymerization conversion rate of preferably 50% by mass or more, more preferably 60% by mass or more. Second stage polymerization; preferably at a temperature of 0-80°C; preferably for a polymerization time of 2-18 hours.
[0059] When the synthesis of the polymer (A) is carried out by three-stage polymerization, it is preferable to set the polymerization in each stage as follows.
[0060] The proportion of the monomers used in the first-stage polymerization is preferably in the range of 20 to 90% by mass, more preferably in the range of 25 to 80% by mass, based on the total mass of the monomers (the sum of the mass of the monomers used in the first-stage polymerization, the mass of the monomers used in the second-stage polymerization, and the mass of the monomers used in the third-stage polymerization). By carrying out the first-stage polymerization at such a proportion of the monomers, particles of the polymer (A) that are excellent in dispersion stability and unlikely to form aggregates can be obtained, and the increase in viscosity over time of the binder composition for an electricity storage device after solidification is also suppressed, which is preferable.
[0061] The types and proportions of monomers used in the second-stage polymerization may be the same as or different from the types and proportions of monomers used in the first-stage polymerization.
[0062] The type and proportion of monomers used in the third-stage polymerization may be the same as or different from the type and proportion of monomers used in the first-stage polymerization and the type and proportion of monomers used in the second-stage polymerization.
[0063] From the viewpoint of the dispersibility of the particles of the resulting polymer (A), the polymerization conditions in each stage are preferably as follows. First-stage polymerization: a temperature of preferably 0 to 80° C.; a polymerization time of preferably 2 to 36 hours; a polymerization conversion rate of preferably 50% by mass or more, more preferably 60% by mass or more. Second stage polymerization; preferably at a temperature of 0-80°C; preferably for a polymerization time of 2-18 hours. Third stage polymerization; preferably at a temperature of 0-80°C; preferably for a polymerization time of 2-9 hours.
[0064] By controlling the total solids concentration in the emulsion polymerization to 50% by mass or less, the polymerization reaction can be carried out in a state in which the dispersion stability of the particles of the obtained polymer (A) is good. This total solids concentration is preferably 45% by mass or less, and more preferably 40% by mass or less.
[0065] Whether the synthesis of the polymer (A) is carried out by single-stage polymerization or multi-stage polymerization, it is preferable to neutralize the polymerization mixture after the emulsion polymerization is completed by adding a neutralizing agent. The neutralizing agent used here is not particularly limited, but examples thereof include metal hydroxides such as sodium hydroxide and potassium hydroxide; ammonia, etc.
[0066] The binder composition for a storage battery device according to this embodiment can be obtained by, for example, replacing the latex aqueous dispersion produced in an aqueous dispersion medium with the dispersion medium, and dispersing the latex aqueous dispersion in a liquid medium (C) that is an organic dispersion medium. In this method, it is necessary to remove water. When the boiling point of the liquid medium (C) is higher than that of water, the liquid medium (C) is added to the obtained latex aqueous dispersion, and the water is removed by evaporating the water using an evaporator or the like. When the liquid medium (C) is an azeotropic medium with water, the liquid medium (C) is added to the obtained latex aqueous dispersion, and the water is azeotroped with water, and the amount of water is reduced to a certain extent using an evaporator or the like, and then the water is removed using a water absorbing agent such as a molecular sieve or a reverse osmosis membrane.
[0067] Another method for producing the binder composition for a power storage device according to this embodiment includes a method in which the polymer (A) produced in an aqueous dispersion medium is once coagulated and dried, then pulverized and dispersed in a liquid medium (C), or a method in which the coagulated and dried polymer (A) is mixed with a liquid medium (C) and pulverized. Dispersion can be performed using a dispersing machine such as a normal ball mill or sand mill; an ultrasonic dispersing machine; a homogenizer, or the like. Furthermore, when the polymer (A) is produced in the liquid medium (C) to obtain a block polymer (A), a particle dispersion of the polymer (A) dispersed in the liquid medium (C) can be obtained by pulverizing the block polymer (A) using a dispersing machine such as a ball mill or sand mill.
[0068] 1.2.Nonionic surfactants (B) The binder composition for an electricity storage device according to this embodiment contains a nonionic surfactant (B). The content of the nonionic surfactant (B) is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 9 parts by mass, and particularly preferably 1 to 8 parts by mass, relative to 100 parts by mass of the polymer (A). It has been found that by containing the nonionic surfactant (B) within the above range, the polymer (A) is more likely to maintain its particle shape in the liquid medium (C). Since the nonionic surfactant (B) has high affinity with both the polymer (A) and the liquid medium (C), the nonionic surfactant (B) adsorbed to the particle interface of the polymer (A) is easily absorbed into the liquid medium (C). C), and its steric hindrance is believed to enable the polymer (A) to maintain its particle shape without agglomerating. The polymer (A) being able to maintain its particle shape can prevent excessive coating on the positive electrode active material and conductive assistant, forming a good conductive path. Furthermore, it can provide flexibility and adhesion inherent to the particles.
[0069] As described above, the nonionic surfactant (B) and other emulsifiers are used when polymerizing the polymer (A), but the amount of residual emulsifier changes depending on the conditions of the subsequent coagulation process, washing process, etc. Therefore, it is common that the residual emulsifier is not properly managed. It has been found that the binder composition for an electric storage device according to this embodiment exhibits good battery characteristics by properly managing the content ratio of the nonionic surfactant (B) in the manufacturing process. That is, when the content ratio of the nonionic surfactant (B) is equal to or less than the upper limit, it is possible to effectively suppress the occurrence of craters due to bubble breakage derived from the emulsifier on the surface of the slurry coating film. In addition, when the content ratio of the nonionic surfactant (B) is equal to or more than the lower limit, the polymer (A) can maintain its particle shape in the liquid medium (C), and a good conductive path is formed in the electrode layer, suppressing the increase in internal resistance, thereby exhibiting good repeated charge and discharge characteristics. In particular, when the electrode layer is unable to maintain the electronic conductive path, the lithium ion conductivity decreases and the resistance increases, so it is important to suppress the inhibition of the conductive path due to the fusion of the particles of the polymer (A).
[0070] Examples of the nonionic surfactant (B) include ether type nonionic surfactants, ester type nonionic surfactants, and ester-ether type nonionic surfactants.
[0071] Examples of ether-type nonionic surfactants include polyoxyalkylene glycols (e.g., polyoxyethylene polyoxypropylene glycols) and types in which an oxyalkylene group (e.g., ethylene oxide) is added to a hydrocarbon group having a hydroxyl group (e.g., polyoxyalkylene alkyl ethers such as polyoxyethylene alkyl ethers; polyoxyethylene phenyl ethers, polyoxyethylene alkyl phenyl ethers, polyoxyethylene styrenated phenyl ethers, etc.). Examples of the hydrocarbon group having a hydroxyl group include alcohol compounds and phenol compounds. Examples of the alcohol compound include linear alkyl alcohols such as methanol, ethanol, propanol, butanol, pentanol, hexanol, octanol, nonanol, decanol, undecanol, dodecanol, tridecanol, tetradecanol, pentadecanol, hexadecanol, heptadecanol, octadecanol, nonadecanol, eicosanol, heneicosanol, docosanol, tricosanol, tetracosanol, pentacosanol, hexacosanol, heptacosanol, octacosanol, nonacosanol, and triacontanol; isopropanol, isobutanol, isohexanol, 2-ethylhexanol, isononanol, isodecanol, isotridecanol, isotetradecanol, and isotridecanol. Examples of the alcohol include branched alkyl alcohols such as acontanol, isohexadecanol, isoheptadecanol, isooctadecanol, isononadecanol, isoeicosanol, isoheneicosanol, isodocosanol, isotricosanol, isotetracosanol, isopentacosanol, isohexacosanol, isoheptacosanol, isooctacosanol, isononacosanol, and isopentadecanol; linear alkenyl alcohols such as tetradecenol, hexadecenol, heptadecenol, octadecenol, and nonadecenol; branched alkenyl alcohols such as isohexadecenol and isooctadecenol; cyclic alkyl alcohols such as cyclopentanol and cyclohexanol, and aromatic alcohols such as benzyl alcohol.Examples of the phenol compound include phenol, alkylphenol, monostyrenated phenol, distyrenated phenol, tristyrenated phenol, etc. Among them, a chain-like higher alcohol having 10 to 20 carbon atoms is preferable, and the number of carbon atoms of the higher alcohol may be 11 to 17, or 11 to 15 (or further 12 to 13).
[0072] The ester-type nonionic surfactant may be one having an ester bond between a polyhydric alcohol and a higher fatty acid. Examples of the polyhydric alcohol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2-methyl-1,2-propanediol, 1,5-pentanediol, 1,6-hexanediol, 2,5-hexanediol, 2-methyl-2,4-pentanediol, 2,3-dimethyl-2,3-butanediol, glycerin, 2-methyl-2-hydroxymethyl-1,3-propanediol, 2-ethyl-2-hydroxymethyl-1,3-propanediol, trimethylolpropane, sorbitan, pentaerythritol, sorbitol, glycerin, and sucrose. Examples of higher fatty acids include linear alkyl carboxylic acids such as octanoic acid, nonanoic acid, decanoic acid, undecanoic acid, dodecanoic acid (lauric acid), tridecanoic acid, tetradecanoic acid (myristic acid), pentadecanoic acid, hexadecanoic acid, heptadecanoic acid, octadecanoic acid (stearic acid), nonadecanoic acid, eicosanoic acid, heneicosanoic acid, and docosanoic acid; branched alkyl carboxylic acids such as 2-ethylhexanoic acid, isododecanoic acid, isotridecanoic acid, isotetradecanoic acid, isohexadecanoic acid, and isooctadecanoic acid; linear alkenyl carboxylic acids such as octadecenoic acid, octadecadienoic acid, octadecatrienoic acid, and oleic acid. Among these, oleic acid, stearic acid, lauric acid, and myristic acid are preferable. Examples of ester-type nonionic surfactants include polyglycerin fatty acid esters, polysorbitan fatty acid esters, and sucrose fatty acid esters.
[0073] Ester-ether type nonionic surfactants include those that have both ester and ether bonds in the molecule (e.g., fatty acid methyl ester ethoxylates). Examples of ester-ether type nonionic surfactants include those in which ethylene oxide is added to esters of polyhydric alcohols such as glycerin and sorbitol and fatty acids, fatty acid polyethylene glycols, and fatty acid polyoxyethylene sorbitan.
[0074] Among these, ether-type nonionic surfactants are preferred, with polyoxyalkylene alkyl ethers and polyoxyalkylene phenyl ethers being more preferred, and polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers and polyoxyethylene distyrenated phenyl ethers being particularly preferred.
[0075] 1.3. Liquid medium (C) The binder composition for an electric storage device according to this embodiment contains a liquid medium (C). The liquid medium (C) is not particularly limited, but may be an aliphatic hydrocarbon such as hexane, heptane, octane, decane, or dodecane; an alicyclic hydrocarbon such as cyclohexane, cycloheptane, cyclooctane, or cyclodecane; an aromatic hydrocarbon such as toluene, xylene, mesitylene, naphthalene, or tetralin; a ketone such as methylhexyl ketone or dipropyl ketone; an ester such as butyl acetate, butyl butyrate, or methyl butanoate; an ether such as dibutyl ether, tetrahydrofuran, or anisole; or a lactam such as N-methyl-2-pyrrolidone or 2-pyrrolidone. These liquid media (C) may be used alone or in combination of two or more.
[0076] The liquid medium (C) may contain water as long as it contains an organic solvent as the main solvent. The term "containing an organic solvent as the main solvent" means that the organic solvent accounts for more than 50% by mass when the total mass of the liquid medium (C) is taken as 100% by mass.
[0077] 1.4. Other Additives The binder composition for an electricity storage device according to this embodiment may contain, as necessary, components other than those described above. Such additives may include, for example, polymers other than the polymer (A) and preservatives.
[0078] <Polymers other than polymer (A)> The binder composition for a storage battery device according to this embodiment may contain a polymer other than the polymer (A). Such a polymer is not particularly limited, but may be an acrylic polymer containing an unsaturated carboxylic acid ester or a derivative thereof as a constituent unit that is soluble in the liquid medium (C), a styrene-butadiene polymer containing a conjugated diene as a constituent unit, an acrylonitrile-butadiene copolymer, a fluorine-based polymer such as PVDF (polyvinylidene fluoride), or the like. These polymers may be used alone or in combination of two or more. By containing these polymers, the slurry has good properties, and the flexibility and adhesion of the electrode may be further improved.
[0079] <Preservatives> The binder composition for a storage battery device according to the present embodiment may contain a preservative. By containing a preservative, it may be possible to suppress the proliferation of bacteria, mold, and the like and the generation of foreign matter when the binder composition for a storage battery device is stored. Specific examples of the preservative include compounds described in Japanese Patent No. 5477610 and the like.
[0080] 2. Slurry for electricity storage devices The slurry for an electric storage device according to one embodiment of the present invention contains the above-mentioned binder composition for an electric storage device. The above-mentioned binder composition for an electric storage device can be used as a material for producing a protective film for suppressing short circuits caused by dendrites that occur during charging and discharging, and can also be used as a material for producing an electrode (active material layer) for an electric storage device that has improved binding ability between active materials, adhesion ability between an active material and a current collector, and resistance to powder falling. Hereinafter, the slurry for an electric storage device for producing a protective film (hereinafter also referred to as "slurry for a protective film") and the slurry for an electric storage device for producing an active material layer of an electrode for an electric storage device (hereinafter also referred to as "slurry for an electric storage device electrode") will be described separately.
[0081] 2.1.Slurry for protective film The "slurry for protective film" refers to a dispersion liquid used to prepare a protective film on the surface of an electrode or a separator or both by applying the slurry to the surface of an electrode or a separator or both and then drying the slurry. The slurry for protective film according to this embodiment may be composed only of the binder composition for a storage battery device described above, or may further contain an inorganic filler. Examples of the inorganic filler include the inorganic fillers described in JP 2020-184461 A.
[0082] 2.2. Slurry for energy storage device electrodes The "slurry for an electric storage device electrode" refers to a dispersion liquid used for preparing an active material layer on the surface of a current collector by applying the dispersion liquid to the surface of the current collector and then drying the same. The slurry for an electric storage device electrode according to this embodiment contains the above-mentioned binder composition for an electric storage device and an active material.
[0083] Hereinafter, the components contained in the slurry for an electricity storage device electrode according to this embodiment will be described.
[0084] 2.2.1. Polymer (A) The composition, physical properties, production method, etc. of the polymer (A) are as described above, so description thereof will be omitted.
[0085] The content of the polymer component in the slurry for an electric storage device electrode according to this embodiment is preferably 1 to 8 parts by mass, more preferably 1 to 7 parts by mass, and particularly preferably 1.5 to 6 parts by mass, relative to 100 parts by mass of the active material. When the content of the polymer component is within the above range, the dispersibility of the active material in the slurry is good, and the coating property of the slurry is also excellent. Here, the polymer component includes the polymer (A) and a polymer other than the polymer (A) that is added as necessary.
[0086] 2.2.2.Active material The active material used in the slurry for the electric storage device electrode according to this embodiment includes a positive electrode active material and a negative electrode active material. Specific examples of these include carbon materials, silicon materials, oxides containing lithium atoms, sulfur compounds, lead compounds, tin compounds, arsenic compounds, antimony compounds, aluminum compounds, conductive polymers such as polyacene, A X B Y O Z (wherein A is an alkali metal or a transition metal, B is at least one selected from transition metals such as cobalt, nickel, aluminum, tin, and manganese, O is an oxygen atom, and X, Y, and Z are numbers within the ranges of 1.10>X>0.05, 4.00>Y>0.85, and 5.00>Z>1.5, respectively.) and other metal oxides. Examples of the composite metal oxide include lithium cobalt oxide, lithium nickel oxide, lithium manganate, and ternary lithium nickel cobalt manganate.
[0087] The slurry for an electricity storage device electrode according to this embodiment can be used when producing either a positive electrode or a negative electrode, but is particularly preferably used for a positive electrode.
[0088] As the positive electrode active material, among the active materials exemplified above, an oxide containing lithium atoms is preferably used. The power storage device electrode produced using the slurry for a power storage device electrode according to the present embodiment can exhibit good electrical characteristics even when an oxide containing lithium atoms is used as the positive electrode active material. The reason for this is considered to be that the polymer (A) can firmly bind the oxide containing lithium atoms and can maintain the state in which the oxide containing lithium atoms is firmly bound even during charge and discharge.
[0089] Examples of the oxide containing lithium atoms include one or more selected from lithium atom-containing oxides (olivine-type lithium-containing phosphate compounds) represented by the following general formula (1) and having an olivine-type crystal structure. Li 1-x M x (AO4) (1) (In formula (1), M is an ion of at least one metal selected from the group consisting of Mg, Ti, V, Nb, Ta, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, Ge, and Sn, and A is at least one selected from the group consisting of Si, S, P, and V, and x is a number satisfying the relationship 0 < x < 1.) Note that the value of x in the general formula (1) is selected so that the valence of the entire general formula (1) becomes 0 in accordance with the valences of M and A.
[0090] Examples of the olivine-type lithium-containing phosphate compound include LiFePO4, LiCoPO4, LiMnPO4, Li 0.90 Ti 0.05 Nb 0.05 Fe 0.30 Co 0.30 Mn 0.30 PO4 and the like. Among these, LiFePO4 (lithium iron phosphate) is particularly preferable because the raw material iron compound is easily available and inexpensive.
[0091] The average particle size of the olivine type lithium phosphate compound is preferably in the range of 0.5 to 30 μm, more preferably in the range of 0.5 to 25 μm, and particularly preferably in the range of 0.5 to 20 μm.
[0092] On the other hand, when preparing a negative electrode, among the active materials exemplified above, it is preferable to use a material containing a silicon material and / or a carbon material, and more preferably a mixture of a silicon material and a carbon material. Since the amount of lithium absorbed per unit weight of a silicon material is larger than that of other active materials, the storage capacity of the resulting power storage device can be increased, and as a result, the output and energy density of the power storage device can be increased. On the other hand, since the volume change of a carbon material accompanying charge and discharge is smaller than that of a silicon material, by using a mixture of a silicon material and a carbon material as a negative electrode active material, the effect of the volume change of the silicon material can be mitigated, and the adhesion ability between the active material layer and the current collector can be further improved.
[0093] 2.2.3.Other ingredients In addition to the above-mentioned components, the slurry for an electricity storage device electrode according to this embodiment may contain, as necessary, a polymer other than the polymer (A), a liquid medium, a conductive assistant, a corrosion inhibitor, cellulose fiber, an antioxidant, etc. The polymer other than the polymer (A) may be appropriately selected from the compounds exemplified in the above section "1.4. Other Additives" and used for the same purpose.
[0094] <Liquid medium> A liquid medium may be further added to the slurry for an electric storage device electrode according to this embodiment in addition to the liquid medium carried over from the binder composition for an electric storage device. The liquid medium to be added may be the same as or different from the liquid medium (C) contained in the binder composition for an electric storage device, but is preferably selected from the liquid media exemplified in the above section "1.3. Liquid medium (C)".
[0095] The content of the liquid medium (including the amount carried over from the binder composition for an electricity storage device) in the slurry for an electricity storage device electrode according to this embodiment is preferably such that the solids concentration in the slurry (meaning the proportion of the total mass of the components in the slurry other than the liquid medium to the total mass of the slurry; the same applies below) is 30 to 90 mass%, and more preferably 40 to 80 mass%.
[0096] <Conductive assistant> A conductive assistant may be further added to the slurry for an electricity storage device electrode according to this embodiment for the purposes of imparting electrical conductivity and buffering the volume change of the active material caused by the ingress and egress of lithium ions.
[0097] Specific examples of the conductive assistant include carbon such as activated carbon, acetylene black, ketjen black, furnace black, graphite, carbon fiber, fullerene, and carbon nanotubes. Among these, acetylene black, ketjen black, and carbon nanotubes can be preferably used. The content of the conductive assistant is preferably 20 parts by mass or less, more preferably 1 to 15 parts by mass, and particularly preferably 2 to 10 parts by mass, relative to 100 parts by mass of the active material.
[0098] <Corrosion inhibitor> A corrosion inhibitor may be further added to the slurry for an electricity storage device electrode according to this embodiment for the purpose of suppressing corrosion of the current collector depending on the type of active material.
[0099] Examples of the corrosion inhibitor include ammonium metavanadate, sodium metavanadate, potassium metavanadate, ammonium metatungstate, sodium metatungstate, potassium metatungstate, ammonium paratungstate, sodium paratungstate, potassium paratungstate, ammonium molybdate, sodium molybdate, and potassium molybdate. Among these, paratungstate is particularly preferred. Among these, ammonium vanadate, ammonium metavanadate, sodium metavanadate, potassium metavanadate, and ammonium molybdate are preferred.
[0100] <Cellulose fiber> The slurry for an electric storage device electrode according to this embodiment may further contain cellulose fibers. Known cellulose fibers may be used. The addition of cellulose fibers may improve the adhesion of the active material to the current collector. It is believed that the fibrous cellulose fibers bond adjacent active materials together in a fibrous form by linear adhesion or linear contact, thereby preventing the active material from falling off and improving the adhesion to the current collector.
[0101] 2.2.4. Method for preparing slurry for power storage device electrodes The slurry for the electric storage device electrode according to the present embodiment may be produced by any method as long as it contains the above-mentioned binder composition for the electric storage device and the active material. From the viewpoint of producing a slurry having better dispersibility and stability more efficiently and inexpensively, it is preferable to produce the slurry by adding the active material and optional additive components used as necessary to the binder composition for the electric storage device and mixing them. Specific examples of the production method include the method described in Japanese Patent No. 5999399.
[0102] 3.Electricity storage device electrodes An electric storage device electrode according to one embodiment of the present invention comprises a current collector and an active material layer formed by applying the above-mentioned slurry for an electric storage device electrode to the surface of the current collector and drying it. Such an electric storage device electrode can be produced by applying the above-mentioned slurry for an electric storage device electrode to the surface of a current collector such as a metal foil to form a coating film, and then drying the coating film to form an active material layer. The electric storage device electrode produced in this manner has excellent adhesion since it is formed by binding an active material layer containing the above-mentioned polymer (A), an active material, and optional components added as necessary to the surface of the current collector, and also has excellent charge / discharge durability characteristics since expansion of the electrode due to repeated charge / discharge is suppressed.
[0103] The current collector is not particularly limited as long as it is made of a conductive material, and examples thereof include the current collectors described in Japanese Patent No. 5999399 and the like.
[0104] 4. Energy storage devices The electric storage device according to one embodiment of the present invention includes the above-mentioned electric storage device electrode, further contains an electrolytic solution, and can be manufactured by a conventional method using components such as a separator. A specific manufacturing method can include, for example, a method in which a negative electrode and a positive electrode are stacked with a separator interposed therebetween, and the stack is rolled or folded according to the shape of the battery to house it in a battery container, and the electrolytic solution is injected into the battery container and sealed. The shape of the battery can be any appropriate shape, such as a coin type, a cylindrical type, a square type, or a laminate type.
[0105] The electrolyte may be liquid or gel, and may be selected from among known electrolytes used in power storage devices that effectively exhibit the function of a battery depending on the type of active material. The electrolyte may be a solution in which an electrolyte is dissolved in a suitable solvent. Examples of such electrolytes and solvents include those described in Japanese Patent No. 5999399.
[0106] The above-mentioned electric storage device can be applied to lithium ion secondary batteries, electric double layer capacitors, lithium ion capacitors, etc., which require discharging at a high current density. Among these, lithium ion secondary batteries are particularly preferred. In the electric storage device electrode and electric storage device according to this embodiment, the members other than the binder composition for electric storage devices are publicly known lithium ion secondary batteries. It is possible to use materials for batteries, electric double layer capacitors, and lithium ion capacitors.
[0107] 5. Working Example The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.
[0108] 5.1. Examples 1 to 12 and Comparative Examples 1 to 6 5.1.1. Preparation of Binder Composition for Electric Storage Device <Example 1> A polymer (A1) dispersion was obtained by one-stage polymerization as shown below. A monomer mixture consisting of 300 parts by mass of water, 40 parts by mass of acrylonitrile, 25 parts by mass of 1,3-butadiene, 15 parts by mass of styrene, 1 part by mass of itaconic acid, 1 part by mass of acrylic acid, 1 part by mass of methacrylic acid, 5 parts by mass of methyl methacrylate, 5 parts by mass of butyl acrylate, 1 part by mass of acrylamide, 1 part by mass of methacrylamide, and 5 parts by mass of sodium styrenesulfonate, 0.05 parts by mass of tert-dodecyl mercaptan as a chain transfer agent, 0.2 parts by mass of sodium dodecylbenzenesulfonate and 4 parts by mass of polyoxyethylene lauryl ether (manufactured by Kao Corporation, product name "Emulgen 147") as emulsifiers, and 0.6 parts by mass of potassium persulfate as a polymerization initiator was added to a reactor, and the mixture was polymerized at 70°C for 10 hours with stirring to obtain a latex of polymer (A1). The conversion rate of the polymer at this time was 98%.
[0109] Next, 80 parts by mass of the obtained latex (20 parts by mass of solid content) and 230 parts by mass of N-methyl-2-pyrrolidone (hereinafter also referred to as "NMP") were added to a recovery flask, and a dehydration process was carried out at 85°C for 6 hours under reduced pressure in an evaporator. Since only water is removed in this dehydration process, polyoxyethylene lauryl ether remains in the binder composition for electricity storage devices. In this way, the binder composition for electricity storage devices of Example 1 was obtained by replacing the dispersion medium from water to NMP. The solid content concentration of the obtained binder composition for electricity storage devices was 8% by mass.
[0110] <Examples 2 to 12 and Comparative Examples 1 to 6> In Examples 2 to 12 and Comparative Examples 1 to 6, each polymer was synthesized by single-stage polymerization in the same manner as in Example 1, except that the types and amounts of monomers were as shown in Tables 1 and 2 below, respectively, and each binder composition for an electricity storage device was obtained in the same manner as in Example 1.
[0111] 5.1.2. Evaluation of physical properties of binder compositions for energy storage devices <Method for measuring polymerization conversion rate> The polymerization conversion in the synthesis of each of the above polymers was measured as follows. After a predetermined time, the reaction solution polymerized was removed and placed in an aluminum dish (X(g)) whose weight had been measured in advance, and the weight (Y(g)) of the reaction solution was measured. This was dried at 155°C for 15 minutes using a hot air dryer. The aluminum dish was removed and allowed to cool, after which the weight (Z(g)) of the aluminum dish was measured. The polymerization conversion rate (%) was calculated from the weights X, Y, and Z thus measured using the following formula (2). Polymerization conversion rate (%) = ((ZX) / Y) × 100 (2)
[0112] <Measurement of number average particle size> The binder composition for an electricity storage device obtained above was diluted with NMP to a solid content of 0.1 wt % to prepare a measurement sample. The measurement sample obtained was measured using a dynamic light scattering method (DLS) under the following conditions to determine the number average particle size of each polymer. ·Temperature: 25℃ NMP refractive index: 1.47
[0113] 5.1.3. Preparation of Lithium-Ion Secondary Battery Positive Electrode Slurry Into a two-shaft planetary mixer (manufactured by Primix Corporation, product name "TK Hivismix 2P-03"), 1 part by mass (solid content equivalent value, added as an NMP solution with a concentration of 8%) of PVdF (manufactured by Arkema, product name "HSV900"), 2 parts by mass of polymer (A) (solid content equivalent value, added as the binder composition for a power storage device obtained above), 100 parts by mass of lithium iron phosphate (manufactured by Tokukata Nabe Co., Ltd., product name "DY-1") as a positive electrode active material, 9 parts by mass of acetylene black, and 13.5 parts by mass of NMP were added, and the solid content concentration was adjusted to a slurry of approximately 70%, and the mixture was stirred at 60 rpm for 1 hour.
[0114] Next, NMP was added to the obtained paste to adjust the solid concentration to 52%, and then the mixture was stirred at 200 rpm for 2 minutes, at 1800 rpm for 5 minutes, and then further stirred under vacuum (approximately 5.0 × 10 3 The mixture was stirred and mixed at 1,800 rpm for 1.5 minutes at 1000 Pa to prepare a slurry for a lithium ion secondary battery positive electrode.
[0115] 5.1.4. Preparation and evaluation of the properties of positive electrodes for lithium-ion secondary batteries <Preparation of positive electrodes for lithium-ion secondary batteries> The slurry for the positive electrode of a lithium ion secondary battery obtained above was uniformly applied by a doctor blade method to the surface of a current collector made of aluminum foil with a thickness of 20 μm so that the film thickness after drying would be 120 μm, and then dried at 120° C. for 20 minutes. After that, the density of the formed film (positive electrode active material layer) was 2.1 g / cm 3 The resultant product was pressed using a roll press machine so as to obtain a positive electrode for a lithium ion secondary battery.
[0116] <Evaluation of electrode condition> The lithium ion secondary battery positive electrode obtained above was cut into a size of 10 cm x 10 cm, and the number of broken bubble marks on the surface was visually counted. The evaluation criteria were as follows. The evaluation results are shown in Tables 1 and 2 below. Those in which no damage was observed in the active material layer had reduced coating defects due to residual emulsifier, and showed good cycle characteristics. (Evaluation Criteria) 5 points: If there are no traces of broken particles, there is absolutely no coating defect due to residual emulsifier and the result is good. 4 points: If the number of traces of broken particles is between 1 and 5, there is almost no coating defect due to residual emulsifier and the result is good. 3 points: If the number of broken particle marks is between 6 and 10, there is little coating failure due to residual emulsifier and it is good. 2 points: If the number of broken particle marks is between 11 and 15, there is some coating defect due to residual emulsifier, making it difficult to use. 1 point: If the number of broken particle marks is 16 or more, there is a lot of coating failure due to residual emulsifier, and the product cannot be used.
[0117] <Evaluation of adhesion strength> On the surface of the positive electrode for lithium ion secondary battery obtained above, ten incisions were made vertically and horizontally at 2 mm intervals to a depth reaching from the active material layer to the current collector, creating a grid pattern. An adhesive tape with a width of 18 mm (manufactured by Nichiban Co., Ltd., product name "Cellotape" (registered trademark), as specified in JIS Z1522:2009) was attached to the incisions and immediately peeled off, and the degree of falling off of the active material was evaluated by visual inspection. The evaluation criteria were as follows. The evaluation results are shown in Tables 1 and 2 below. (Evaluation Criteria) 5 points: No active material layers fell off. 4 points: 1 to 5 pieces of the active material layer are missing. 3 points: 6 to 20 pieces of the active material layer have fallen off. 2 points: 21 to 40 pieces of the active material layer fell off. 1 point: 41 or more pieces of the active material layer are missing.
[0118] 5.1.5. Fabrication and property evaluation of lithium-ion secondary batteries <Preparation of slurry for negative electrodes of lithium-ion secondary batteries> One part by mass (converted to solids) of a thickener (product name "CMC2200", manufactured by Daicel Corporation), 100 parts by mass (converted to solids) of graphite as a negative electrode active material, and 68 parts by mass of water were added to a two-shaft planetary mixer (manufactured by Primix Corporation, product name "TK Hivismix 2P-03") and stirred at 60 rpm for 1 hour.
[0119] Next, SBR (trade name "TRD105A", manufactured by ENEOS Material Co., Ltd.) was added in an amount equivalent to 2 parts by mass (solid content equivalent), and further stirred for 1 hour to obtain a paste. Water was added to the obtained paste to adjust the solid content to 50%, and then a stirring and defoaming machine (manufactured by Thinky Corporation, trade name "Awatori Rentaro") was used to stir and mix at 200 rpm for 2 minutes, at 1800 rpm for 5 minutes, and further at 1800 rpm for 1.5 minutes under vacuum to prepare a slurry for the negative electrode of a lithium ion secondary battery.
[0120] <Preparation of negative electrodes for lithium-ion secondary batteries> The slurry for lithium ion secondary battery negative electrode prepared above was uniformly applied to the surface of a current collector made of copper foil with a thickness of 20 μm by a doctor blade method so that the film thickness after drying would be 80 μm, and then dried at 120° C. for 20 minutes. After that, the density of the formed film (negative electrode active material layer) was 1.9 g / cm 3 The negative electrode for a lithium ion secondary battery was obtained by pressing the negative electrode using a roll press machine so that the negative electrode became
[0121] <Assembling lithium-ion secondary batteries> In a glove box substituted with Ar gas so that the dew point was -80°C or less, the lithium ion secondary battery negative electrode prepared above was punched out into a circle with a diameter of 16.16 mm and placed on a two-electrode coin cell (manufactured by Hosen Co., Ltd., product name "HS Flat Cell"). Next, a separator made of a polypropylene porous film punched out into a circle with a diameter of 24 mm (manufactured by Celgard Co., Ltd., product name "Celgard #2400") was placed on top of the lithium ion secondary battery negative electrode. Furthermore, 500 μL of electrolyte was poured in to prevent air from entering, and then the lithium ion secondary battery positive electrode prepared above was punched out into a circle with a diameter of 15.95 mm and placed on top of the separator, and the exterior body of the two-electrode coin cell was screwed and sealed to assemble a lithium ion secondary battery. The electrolyte used here was a solution in which LiPF6 was dissolved at a concentration of 1 mol / L in a solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 1 (mass ratio).
[0122] <Evaluation of resistance increase rate> The lithium ion secondary battery prepared above was charged at a constant current (1.0C) in a thermostatic chamber adjusted to 25°C, and when the voltage reached 3.8V, charging was continued at a constant voltage (3.8V), and charging was completed (cut-off) when the current value reached 0.01C. Discharge was then started at a constant current (0.05C), and charging was completed (cut-off) when the voltage reached 2.0V, and the discharge capacity at the 0th cycle was calculated. Furthermore, charging was started at a constant current (1.0C), and charging was continued at a constant voltage (3.8V) when the voltage reached 3.8V, and charging was completed (cut-off) when the current value reached 0.01C. Discharge was then started at a constant current (1.0C), and discharging was completed (cut-off) when the voltage reached 2.0V, and the discharge capacity at the 1st cycle was calculated. In this manner, 100 charge-discharge cycles were performed. After 100 charge / discharge cycles, the battery was charged / discharged in the same manner as in the 0th cycle, and the discharge capacity in the 101st cycle was evaluated. The resistance increase rate was calculated by the following formula (3), and the battery was evaluated according to the following criteria. The results are shown in Tables 1 and 2 below. Resistance increase rate (%) = (discharge capacity at 101st cycle - discharge capacity at 100th cycle) / (discharge capacity at 0th cycle - discharge capacity at 1st cycle) x 100 (3) (Evaluation Criteria) 5 points: Resistance increase rate is between 100% and 110%. 4 points: Resistance increase rate is between 110% and 120%. 3 points: Resistance increase rate is between 120% and 130%. 2 points: Resistance increase rate is between 130% and 140%. 1 point: Resistance increase rate is between 140% and 150%. 0 points: Resistance increase is 150% or more.
[0123] <Evaluation of cycle characteristics> The lithium ion secondary battery prepared above was charged at a constant current (1.0 C) in a thermostatic chamber adjusted to 25° C., and when the voltage reached 3.8 V, charging was continued at a constant voltage (3.8 V). The charging was completed (cut off) when the current value reached 0.01 C. Thereafter, discharging was started at a constant current (1.0 C), and the discharging was completed (cut off) when the voltage reached 2.0 V, and the discharge capacity of the first cycle was calculated. In this manner, charging and discharging were repeated 100 times. The capacity retention rate was calculated using the following formula (4) and evaluated according to the following criteria. The results are shown in Tables 1 and 2 below. Capacity retention rate (%) = (100th cycle discharge capacity) / (1st cycle discharge capacity) (4) (Evaluation Criteria) 5 points: Capacity retention is 95% or more. 4 points: Capacity retention is between 90% and 95%. 3 points: Capacity retention is between 85% and 90%. 2 points: Capacity retention is between 80% and 85%. 1 point: Capacity retention is between 75% and 80%. 0 points: Less than 75% capacity retention.
[0124] 5.2. Examples 13 to 19 and Comparative Example 7 In Example 13, 80 parts by mass (20 parts by mass of solid content) of the latex of the polymer (A3) synthesized in Example 3 and 230 parts by mass of γ-butyrolactone were added to an eggplant flask, and a dehydration step was carried out at 85 °C for 6 hours under reduced pressure with an evaporator. In this way, except that the dispersion medium was replaced from water to γ-butyrolactone to obtain the binder composition for a power storage device of Example 13, the same evaluation as in Example 3 was carried out. The solid content concentration of the obtained binder composition for a power storage device was 8% by mass.
[0125] In Examples 14 to 19, a binder composition for a power storage device was obtained in the same manner as in Example 3 except that the dispersion medium was replaced from water to the liquid medium (C) described in Table 3 below, and the same evaluation as in Example 3 was carried out. In Comparative Example 7, a binder composition for a power storage device was obtained in the same manner as in Example 3 except that the latex of the polymer (A3) synthesized in Example 3 was diluted with water so that the solid content concentration became 8% by mass, and the same evaluation as in Example 3 was carried out.
[0126] 5.3. Examples 20 to 25 A binder composition for a power storage device was obtained in the same manner as in Example 3 except that the contents of PVdF and the polymer (A3) contained in the slurry for a lithium ion secondary battery positive electrode were the amounts described in Table 4 below, and the same evaluation as in Example 3 was carried out.
[0127] 5.4. Examples 26 to 28 A binder composition for a power storage device was obtained in the same manner as in Example 3 except that NBR, SBR, or an acrylic polymer soluble in NMP was used instead of PVdF, and the same evaluation as in Example 3 was carried out. Synthesis examples of each polymer used in Examples 26 to 28 are shown below.
[0128] <Synthesis of NBR> An NBR dispersion was obtained by one-step polymerization as shown below. A reactor was charged with 200 parts by mass of water, a monomer mixture consisting of 50 parts by mass of 1,3-butadiene, 5 parts by mass of methacrylic acid, and 45 parts by mass of acrylonitrile, 0.5 part by mass of tert-dodecyl mercaptan as a chain transfer agent, 1 part by mass of sodium dodecylbenzenesulfonate as an emulsifier, 0.02 part by mass of cumene hydroperoxide, 0.01 part by mass of tetrasodium ethylenediaminetetraacetate, 0.006 part by mass of iron(II) sulfate heptahydrate, and 0.03 part by mass of sodium formaldehyde sulfoxylate as a polymerization initiator, and polymerized at 15°C for 10 hours with stirring to obtain an NBR dispersion. The conversion rate of the polymer at this time was 71%.
[0129] Next, 1 part by mass of 2,6-di-tert-butyl-p-cresol was added as an antioxidant, and the NBR dispersion was dropped into 3000 parts by mass of a 0.5% aqueous calcium chloride solution. The obtained aggregates were washed with water, a part of the obtained aggregates was dried at 80°C, and the amount of emulsifier contained in the aggregates was analyzed. Thereafter, the same operation was repeated, and when no decrease in the amount of emulsifier remaining in the aggregates was observed, all the remaining aggregates were dried at 80°C and recovered in total.
[0130] The NBR obtained above was added to NMP and stirred overnight to prepare an NBR solution in which NBR was dissolved in NMP. Here, when the total amount of this NBR solution was set to 100% by mass, it was adjusted so that the NBR content became 8% by mass.
[0131] <Synthesis of SBR> An SBR dispersion was obtained by one-stage polymerization as shown below. A monomer mixture consisting of 200 parts by mass of water, 50 parts by mass of 1,3-butadiene, and 50 parts by mass of styrene, 0.5 parts by mass of tert-dodecyl mercaptan as a chain transfer agent, 3 parts by mass of sodium alkyl diphenyl ether sulfonate as an emulsifier, 0.02 parts by mass of cumene hydroperoxide, 0.01 parts by mass of tetrasodium salt of ethylenediaminetetraacetic acid, 0.006 parts by mass of iron (II) sulfate heptahydrate, and 0.03 parts by mass of sodium formaldehyde sulfoxylate were charged into a reactor, and the mixture was polymerized at 15°C for 10 hours with stirring to obtain an SBR dispersion. The conversion rate of the polymer at this time was 73%.
[0132] Next, 1 part by mass of 2,6-di-tert-butyl-p-cresol was added as an antioxidant, and the SBR dispersion was dropped into 3,000 parts by mass of a 0.5% aqueous calcium chloride solution. The resulting aggregate was washed with water, and a part of the resulting aggregate was dried at 80°C, and the amount of emulsifier contained in the aggregate was analyzed. The same procedure was then repeated, and when no reduction in the amount of emulsifier remaining in the aggregate was observed, the remaining aggregate was all dried at 80°C and the entire amount was recovered.
[0133] The polymer SBR obtained above was added to NMP and stirred overnight to prepare an SBR solution in which SBR was dissolved in NMP. The SBR content was adjusted to 8% by mass when the entire SBR solution was taken as 100% by mass.
[0134] <Synthesis of acrylic polymer> An acrylic polymer dispersion was obtained by one-stage polymerization as shown below. A reactor was charged with 500 parts by mass of water, a monomer mixture consisting of 64 parts by mass of 2-ethylhexyl acrylate, 1 part by mass of styrene, 5 parts by mass of acrylic acid, and 30 parts by mass of acrylonitrile, 0.5 parts by mass of tert-dodecyl mercaptan as a chain transfer agent, and dodecylbenzene sulfonate as an emulsifier. 1 part by mass of sodium persulfate and 0.3 parts by mass of potassium persulfate as a polymerization initiator were added, and polymerization was carried out for 8 hours at a polymerization temperature of 75° C. to obtain an acrylic polymer dispersion. The conversion rate of the polymer at this time was 99%.
[0135] Next, 1 part by mass of 2,6-di-tert-butyl-p-cresol was added as an antioxidant, and the acrylic polymer dispersion was dropped into 3000 parts by mass of a 0.5% aqueous calcium chloride solution. The resulting aggregate was washed with water, and a part of the resulting aggregate was dried at 80°C, and the amount of emulsifier contained in the aggregate was analyzed. The same procedure was then repeated, and when no reduction in the amount of emulsifier remaining in the aggregate was observed, the remaining aggregate was all dried at 80°C and the entire amount was collected.
[0136] The acrylic polymer obtained above was added to NMP and stirred overnight to prepare an acrylic polymer solution in which the acrylic polymer was dissolved in NMP. The content of the acrylic polymer was adjusted to 8% by mass when the entire acrylic polymer solution was taken as 100% by mass.
[0137] 5.5.Evaluation Results Tables 1 and 2 below show the polymer compositions, property measurement results, and evaluation results used in Examples 1 to 12 and Comparative Examples 1 to 6. Table 3 below shows the lithium ion secondary battery positive electrode slurry compositions used in Examples 13 to 19 and Comparative Example 7, and the evaluation results. Table 4 below shows the lithium ion secondary battery positive electrode slurry compositions used in Examples 20 to 25, and the evaluation results. Table 5 below shows the lithium ion secondary battery positive electrode slurry compositions used in Examples 26 to 28, and the evaluation results. The numerical values showing the compositions shown in Tables 1 to 5 below represent parts by mass.
[0138] [Table 1]
[0139] [Table 2]
[0140] [Table 3]
[0141] [Table 4]
[0142] [Table 5]
[0143] The polymer numbers synthesized in each example are shown in the lines below the Example numbers and Comparative Example numbers in Tables 1 and 2. The monomers, emulsifiers, and polymers in Tables 1 to 5 respectively represent the following compounds. <Monomer> (α,β-unsaturated nitrile compound) ·AN: Acrylonitrile ·MAN: Methacrylonitrile (Conjugated diene compounds) BD: 1,3-butadiene (Unsaturated Carboxylic Acid) ·TA: Itaconic acid ·AA: Acrylic acid ·MAA: Methacrylic acid (Aromatic vinyl compounds) ST: Styrene ·DVB: Divinylbenzene (Unsaturated carboxylic acid ester) MMA: Methyl methacrylate ·BA: Butyl acrylate 2EHA: 2-Ethylhexyl acrylate CHMA: Cyclohexyl methacrylate ·HEMA: Hydroxyethyl methacrylate ·HEA: Hydroxyethyl acrylate ((Meth)acrylamide) ·AAM: Acrylamide ·MAM: Methacrylamide (Compounds having sulfonic acid groups) ·NaSS: Sodium styrene sulfonate <Emulsifier> (Sulfonic acid emulsifier) Sodium alkyldiphenyl ether sulfonate: Trade name "Pelex SS-L", manufactured by Kao Corporation Sodium dodecylbenzenesulfonate: Trade name "Neopelex G-65", manufactured by Kao Corporation (Carboxylic acid emulsifier) Semi-hardened beef tallow fatty acid soda soap: Product name "NS Soap", manufactured by Kao Corporation Potassium rosinate: Trade name "Diprosin A-100", manufactured by Toho Chemical Industry Co., Ltd. (Nonionic surfactant) Polyoxyethylene lauryl ether: Trade name "Emulgen 147", manufactured by Kao Corporation Polyoxyethylene alkyl ether: Trade name "Emulgen 1108", manufactured by Kao Corporation Polyoxyalkylene alkyl ether: Product name "Emulgen LS-110", manufactured by Kao Corporation Polyoxyethylene distyrenated phenyl ether: Trade name "Emulgen A-90", manufactured by Kao Corporation <Polymer> PVdF: Product name "HSV900", manufactured by Arkema, polyvinylidene fluoride
[0144] In Examples 1 to 28, the slurry for the positive electrode of the lithium ion secondary battery contains the binder composition for the power storage device of the present invention and an active material. As a result, it was confirmed that the active material layer formed by the slurry has a good surface condition, and that the active material layer itself does not become brittle during the measurement of the peel strength, causing the active material to fall off or cracks, and that the binder has sufficient binding properties. It was also confirmed that the resistance increase rate of the obtained lithium ion secondary battery is low and the cycle characteristics are improved. It is considered that the slurry for the positive electrode of the lithium ion secondary battery contains an appropriate amount of nonionic surfactant (B), which allows the polymer (A) to maintain its particle shape in the liquid medium (C), and a good conductive path is formed in the formed active material layer, thereby reducing the resistance increase rate and improving the cycle characteristics. Therefore, it was found that by using the binder composition for the power storage device of the present invention, a positive electrode for a lithium ion secondary battery having excellent surface condition, adhesion, and ionic conductivity can be produced, and the cycle characteristics of the lithium ion secondary battery can be improved.
[0145] In Examples 13 to 19 and Comparative Example 7, a slurry for a lithium ion secondary battery positive electrode containing a liquid medium other than NMP is used. As a result, it was found that when a slurry for a lithium ion secondary battery positive electrode containing a specific organic solvent is used, a positive electrode for a lithium ion secondary battery excellent in surface condition, adhesion, and ionic conductivity can be produced, and the cycle characteristics of the lithium ion secondary battery can be improved. On the other hand, when a slurry for a lithium ion secondary battery positive electrode containing water is used, good results were not obtained.
[0146] In Examples 20 to 25, slurries for lithium ion secondary battery positive electrodes in which the content ratio of PVdF and / or polymer (A3) was appropriately changed were used. As a result, it was found that in all Examples, a lithium ion secondary battery positive electrode excellent in surface condition, adhesion, and ionic conductivity could be prepared, and the cycle characteristics of the lithium ion secondary battery could be improved.
[0147] In Examples 26 to 28, a slurry for a lithium ion secondary battery positive electrode using NBR, SBR, or an acrylic polymer soluble in NMP instead of PVdF is used. As a result, in each Example, it was found that a lithium ion secondary battery positive electrode excellent in surface condition, adhesion, and ionic conductivity can be produced, and the cycle characteristics of the lithium ion secondary battery can be improved.
[0148] The present invention is not limited to the above-described embodiments, and various modifications are possible. The present invention includes configurations that are substantially the same as those described in the embodiments (for example, configurations with the same functions, methods, and results, or configurations with the same purpose and effect). The present invention also includes configurations in which non-essential parts of the configurations described in the above-described embodiments are replaced with other configurations. Furthermore, the present invention also includes configurations that have the same effects as the configurations described in the above-described embodiments, or that can achieve the same purpose. Furthermore, the present invention also includes configurations in which publicly known technology is added to the configurations described in the above-described embodiments.
Claims
1. The composition comprises a polymer (A), a nonionic surfactant (B), and a liquid medium (C), When the total amount of repeating units contained in the polymer (A) is taken as 100 mass%, the polymer (A) 1 to 50% by mass of a repeating unit (a1) derived from an α,β-unsaturated nitrile compound; 25 to 75% by mass of a repeating unit (a2) derived from a conjugated diene compound; Contains the content ratio of the nonionic surfactant (B) is 0.1 to 10 parts by mass based on 100 parts by mass of the polymer (A), The binder composition for an electrical storage device, wherein the liquid medium (C) is at least one selected from the group consisting of aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, ketones, esters, ethers, and lactams.
2. The polymer (A) is a polymer particle, The binder composition for a storage battery device according to claim 1 , wherein the polymer particles have a number average particle size of 50 nm or more and 1,000 nm or less.
3. 3. The binder composition for a storage battery device according to claim 1, wherein the polymer (A) further contains 0.1 to 10 mass % of a repeating unit (a3) derived from an unsaturated carboxylic acid.
4. The binder composition for a storage battery device according to claim 1 or 2, wherein the polymer (A) further contains 1 to 50 mass % of a repeating unit (a4) derived from an aromatic vinyl compound.
5. 3. The binder composition for an electrical storage device according to claim 1, wherein the polymer (A) further contains 0.1 to 10 mass % of a repeating unit (a6) derived from (meth)acrylamide.
6. The binder composition for a storage battery device according to claim 1 or 2, wherein the polymer (A) further contains 0.1 to 10 mass % of a repeating unit (a7) derived from a compound having a sulfonic acid group.
7. A slurry for an electrode of an electricity storage device, comprising the binder composition for an electricity storage device according to claim 1 or 2 and an active material.
8. The slurry for an electricity storage device electrode according to claim 7 , further comprising a thickener.
9. The slurry for an electric storage device electrode according to claim 7 , wherein the active material is a positive electrode active material.
10. The slurry for an electric storage device electrode according to claim 9 , wherein the positive electrode active material is an olivine-type lithium-containing phosphate compound.
11. 10. An electricity storage device electrode comprising: a current collector; and an active material layer formed by applying the slurry for an electricity storage device electrode according to claim 7 to a surface of the current collector and drying the slurry.
12. An electricity storage device comprising the electricity storage device electrode according to claim 11.
Citation Information
Patent Citations
Binder for battery binder solution, electrode mixture, electrode structure and battery
JP1998298386A
Binder composition for power storage device
JP2019194944A